If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + x = 33 Solving 7 + x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 33 + -7 Combine like terms: 7 + -7 = 0 0 + x = 33 + -7 x = 33 + -7 Combine like terms: 33 + -7 = 26 x = 26 Simplifying x = 26
| 4y=4-8/17 | | -12-2x=2x+18 | | 60/17+4y=8 | | 2(m-5)+12=3m | | 3x-9=3.5x-9 | | 2=3x^2+x-2 | | (X-1)-1.4=6.2 | | 3(x-1)=-15 | | x^2+25x=7500 | | 16-(5y-3y)=2 | | 0=3x^2+x-2 | | 11x+7.6+5x+9x-2= | | p/s-q/s=1 | | xln=-1 | | -9(x)=-63 | | 7*13*6*x=57*19 | | 4x^2+8y=40 | | 5(x-9)/2+3/4=2x+2 | | ln(2x+1)+ln(x+3)=0 | | 7+13-6+x=57-19 | | 33=x+7 | | 5=x-2/5 | | x^3-8x^2-10x+20=0 | | 3(x)=24 | | 12x+x(2-4)=0 | | 4(2-5)= | | 4y^2-96y+576=0 | | (x^2+x*y-y^2)dx(-x*y)dy=0 | | 3x^2+12x-495=0 | | 5+2/x+1=14 | | 5-2/x=3 | | a^2-10a+25=36 |